Pengaruh Kondisi Ekonomi Keluarga terhadap Motivasi Belajar Mahasiswa Program Studi Pendidikan Ekonomi FKIP Universitas Nias - Gulo, Dewi Juliana; Telaumbanua, Wahyutra Aldiman; Laoli, Eka Septianti; Lase, Asali (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This study aims to analyze the effect of family economic conditions on student learning motivation in the Economics Education Study Program at FKIP, Nias University. This study used a descriptive quantitative approach with a population of 190 students, and through the simple random sampling method and the Slovin formula, a sample of 66 people was obtained. Data were collected using questionnaires and documentation, which were then analyzed through validity, reliability, correlation coefficient, coefficient of determination, simple linear regression, and hypothesis testing. The results showed that the questionnaire used had high reliability, with an rii value for variable X of 0.776 and variable Y of 0.814. Simple linear regression analysis resulted in the equation Y = 46.83 + 0.218X, which shows that family economic conditions have a positive effect on learning motivation. The coefficient of determination of 4.84% shows that the effect of family economic conditions on learning motivation is low but significant. Hypothesis testing shows that tcount = 1.804 is greater than ttable = 1.669, so Ha is accepted and Ho is rejected. In conclusion, there is a significant influence between family economic conditions on student learning motivation in the Economic Education Study Program at FKIP Nias University Academic Year 2023/2024.